Kebijakan Pendidikan Anti Korupsi di Perguruan Tinggi - Kadir, Yusrianto (Universitas Gorontalo)
Reasoning various negative perceptions towards the direction of national education that has been considered not to characterize the national personality, especially about the output of education that tends not to reflect the values and principles of anti-corruption in work and daily, so that through formal education there should be an increase in terms of intensity. Simplistically, the formal education sector in Indonesia can play a role in meeting the need for corruption prevention. Preventive measures can indirectly pass through two approaches, first: targeting learners, and second: using the empowerment of learners to reduce the environment from permissive to corruption.As for the problems in this paper is how the anti-corruption education policy in Higher Education and the extent of anti-corruption education policies in the prevention of corruption. With the aim to understand and analyze the role of anti-corruption education in growing the values and principles of anti-corruption from an early age.Through this anti-corruption education will be a provision for students to act honestly in the work. Of course, in order not to commit acts of corruption when later occupied a strategic position in an institution or served an important position in this bureaucracy. The facts show that highly educated people are vulnerable to the temptations of corruption because they usually occupy strategic positions in an institution or hold important positions in the bureaucracy.